TOP WOMAN: Identifying barriers to women's access to management. Issue 1 (February 2022) - Ramos, Amparo; Latorre, Felisa; Tomás, Inés; Ramos, José
Abstract: Despite some recent advances, women face more difficulties in accessing management positions. Previous research analyzed several types of barriers contributing to the maintenance of the glass ceiling, including factors such as gender stereotypes, difficulties in work–family balance, human resource policies, difficulties in accessing networks, organizational culture, and higher demands for women to demonstrate their value. The perception of the gender barriers can be different or may have a different value depending on the characteristics of specific organizations, teams, jobs, and employees. In this study, we develop the scale "TOP WOMAN" (Testing the Obstacles to Promotion of WOmen to MANagement) to measure barriers to women's promotion. The TOP WOMAN scale was carried out in a large sample from the financial sector in Spain (n = 1304 workers). The scale, composed of 33 items, identified seven dimensions: differential performance appraisal, gender stereotypes, work–family balance, motivational barriers, unfair human resource practices, organizational culture barriers, and barriers to accessing influential networks. The TOP WOMAN scale offers a practical tool to human resource managers to analyze the situation of gender discrimination and to implement best practices in their own organization.